Professional padel: Comparative gender analysis of game transitions during matches - Sánchez-Alcaraz, B.; Sánchez-Pay, A.; Hernández, A.; Martínez-Gallego, R.; Crespo, M.; Ramón-Llin, J. (International Journal of Sports Science & Coaching, 2024)
Transitions, or movements in which players move from attacking to defending situations or vice versa, are key situations in high-performance competitive padel, and therefore, they should be specifically trained. The aim of this study was to analyse the transitions made by players from the back of the court to the net in professional padel and compare them by gender. A total of 1350 points from 14 matches from the 2020 World Padel Tour were analysed, in which 32 professional players (16 men and 16 women) participated. The matches were analysed through systematic observation, using the Lince and Kinovea programmes. Results showed that one or no transitions were made in more than 50% of the points. The first transition was made between fifth and sixth shots of the rally, with a higher percentage of points with more than three transitions in women's matches than in men's matches. Counter-attack transitions were done mainly by the serving partner, most frequently using the lob. The most effective counter-attacks were those in which both players approached the net and both defenders moved to the backcourt, with the women teams obtaining the best results in this type of movement as compared to men. On the other hand, men lost the net less often than women. It is concluded that the results can provide useful guidelines for coaches when prescribing and conducting specific training sessions and individualised match preparation strategies.